A guide to evidence-based group work - Macgowan, Mark J. (Oxford : Oxford University Press, 2008)
Illustrating how to conduct evidence-based group work, this textbook teaches students how to apply best practices through practical learning activities, case examples, research designs step-by-step guidelines and checklists, assessment tips, and detailed instructions for formulating questions and evaluating answers.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social group work; Evidence-based social work